EFICIÊNCIA ENERGÉTICA NAS ESCOLAS PÚBLICAS DO ESTADO DO ACRE: ESTUDO DE CASO DA ESCOLA GLÓRIA PERES - Veras, Aluizio Antonio (2010)
This paper presents a study to evaluate and systematize the rational and efficient use of electricity end uses in the public schools of the State of Acre, focuses on an analysis of wiring in schools. Measurements were made on the premises and removal of end uses such as lighting, air conditioning, computers and other equipment. Procedures are presented for removing the potential for conservation and sketches of the situation existing lighting in classrooms, to examine the illuminance of the existing potential for energy conservation electric end use analysis. The practical application is shown in the form of a case study, conducted in school Glória Peres, considered a model school in the state of Acre, located in Rio Branco, capital of Acre. This paper presents the concept of regulation, far from being merely academic interest, it is essential in order to define the powers of the organs and public bodies that perform this function.